Analysis of Chemical Inventory Control in the GGCP Unit Using Forecasting and EOQ Methods at PT. XYZ - Hisyam Aziz Aditya; Moch. Nuruddin; Yanuar Pandu Negoro (Advance Sustainable Science Engineering and Technology, 2023)
PT. XYZ is a company operating in the energy producing industry. Which has 2 types of products, steam power and electricity. Steam in GGCP contains 3 chemicals, namely Amine, phosphate, oxygen scavenger. However, this company experienced an accumulation of excessive chemical stocks and reduced chemical consumption. This research aims to determine the number of company orders and determine overall inventory costs using forecasting methods and economical order quantities. In calculating the Total Inventory Cost (TIC) results, there is a significant calculation where TIC EOQ has an economical cost for Amine chemicals of IDR. 15,879,937 while the company's TIC is IDR. 36,226,539. with forecast results for Amine chemicals of 4148/ltr, phosphate of 3061/ltr, and scavenger oxygen of 5450/ltr. Meanwhile, the EOQ calculation results obtained a value for Amine chemicals of 1361/ltr, phosphate of 1164/ltr and 1554/ltr for oxygen scavenger chemicals.